Analysis of electrostatic precipitators plate-wire type in reducing dust emissions for sustainable environment - Herliati Rahman; Cepy Hidayaturrahman (Center for Science and Technology, IAIN Surakarta, 2023)
The current global environmental trend is that the world has agreed to go towards net zero emissions. Consequently, waste-producing-industries must comply with these provisions to achieve the mission of sustainable development and green production, including cement industry. This study aims to investigate the factors that affect the performance of the Electrostatic Precipitator (EP) as a dust collector in grinding cement raw materials. The method used was measuring the static-dynamic pressure at the poking hole closest to the EP inlet, measuring EP efficiency using the Matts-Ohnfeldt equation based on secondary data obtained from the Crane Information Management System (CIMS), and calculating the corona power to determine how strong the ion space is created between the discharge electrode and collecting electrode and determine the critical voltage and application voltage needed to generate the corona. The observations and calculations show that several factors can affect EP performance, such as inlet temperature gas discharge, concentration of dust from the chimney, and maximum concentration of chimney outlet. The maximum temperature gas discharge that EP can accept is 105Â°C. The maximum concentration of chimney outlet dust is 50 mg/Nm3 and maximum CO concentration is 2000 mg/m3.